Pengaruh Manajemen Pondok Pesantren Salafi terhadap Prestasi Beajar Siswa pada Mata Pelajaran Fiqih di MA Al-Islah Cikeusal - Zohriah, Anis; Bachtiar, Machdum; Junaedi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to obtain an overview of the influence of salafi Islamic boarding school education management on student achievement in MA Al-Islah. The educational background of children at salafi Islamic boarding schools is a supporting factor for student achievement. Because in salafi Islamic boarding schools, children study a lot of religious knowledge taught by a kiyai. Learning achievement is evidence of learning success or one's ability to carry out learning activities in accordance with the weight achieved. The question is how does the educational background of children at Salafi Islamic boarding schools affect student achievement at MA Al-Islah Cikeusal. Based on the background of the problems above, the formulation The problems in this study are: 1) What are the differences between children who study at salafi Islamic boarding schools and children who do not study at salafi Islamic boarding schools? 2) How is student achievement in fiqh subjects at MA Al-Islah Cikeusal? 3) What is the influence of the educational background of children in salafi Islamic boarding schools on student achievement in fiqh subjects at MA Al-Islah Cikeusal? The aims of this study were: 1) to find out the differences between children who study at salafi Islamic boarding schools and children who do not study at salafi Islamic boarding schools 2) to determine student achievement in fiqh subjects at MA Al-Islah Cikeusal. 3) to determine the effect of the educational background of children in salafi Islamic boarding schools on student achievement in fiqh subjects at MA Al-Islah Cikeusal. This research was conducted at MA Al-Islah Cikeusal. With a total sample of 40 people from a population of 200 students. The population was taken from all students of class XI and class XII MA Al-Islah Cikeusal. The method used is field research, namely research conducted directly to the subject through a questionnaire technique, a series of questions that must be answered by the respondent. The approach used in this thesis is a correlational analysis approach, namely testing the effect of the educational background of children in salafi Islamic boarding schools (Variable X) on student achievement (Variable Y) using the product moment correlation formula. The conclusions obtained from the results of this study are: Based on the results of correlation analysis using Product Moment, it shows a correlation position of rxy 0.31. This shows a low correlation, this is shown by the results of 41.39 th which is greater than tt 0.95, so tcount is greater than ttable. As for the influence of the contribution (coefficient of determination) of the educational background of children in salafi Islamic boarding schools (Variable X) on student achievement (Variable Y) of 9.61%, the remaining 90.39% is influenced by other factors that can be re-examined both internally and externally. external. Keywords: Management, Islamic Boarding School, Learning Achievement